Anchoring Legal Standards. Issue 2 (June 2016) - Feldman, Yuval; Schurr, Amos; Teichman, Doron
Abstract : This article presents the first empirical study on whether anchors influence the interpretation of vague legal standards. To test this question, the article presents a series of stylized experiments that measure and compare participants' interpretation of a vague norm after they were exposed to anchors. Overall, the results suggest that the content of substantive legal rules might be altered by anchors. This effect is documented in numerous legal settings (e.g., torts, corporate, copyright) and across both expert (i.e., experienced lawyers) and nonexpert (i.e., students) populations. Furthermore, the effect is shown to exist both when participants express judgments on a numeric scale and when they make dichotomous judgments that are detached from that scale. Based on these findings, the article revisits several long‐standing legal debates and reevaluates their conclusions.